Flavour in food - Voilley, Andrée; Etiévant, P. (CRC Press ; Woodhead Pub., 2006)
The first part of the book reviews the way flavour is detected and measured. The first two chapters discuss our understanding of how humans perceive and then process information about taste compounds. Chapter three reviews current practice in the sensory analysis of food flavour. Chapter four discusses choosing from the wide range of instrumental techniques which have been developed to identify aroma compounds. The final chapter in Part One discusses the complex issues in matching instrumental measurements with the results of sensory evaluation of foods. Part two reviews key research in the way flavour compounds are retained within foods and the factors determining the way they are released. There are chapters on flavour compound interactions with lipids, emulsions, protein and carbohydrate components in food. Other chapters review modelling aroma interactions in food matrices and mechanisms of flavour retention in and release from liquid food products. The final part reviews what we now know about how humans experience flavour release, together with some of the key factors influencing this process. There are chapters on the process of flavour release in the mouth, the way texture-aroma and odour-taste interactions influence this process, psychological factors and the development of flavour perception during infancy. Flavour in food seeks to distil key developments in flavour science and summarise their implications for the food industry. It is a valuable reference for R & D staff, those responsible for sensory evaluation of foods and product development, as well as academics and students involved in flavour science. Understand how flavour is detected and measuredAnalyses key research in the retention and release of flavour compoundsExamines how humans experience flavour release.
Keywords: Flavor.; Food -- Analysis.; elektronické knihy; electronic books